Unveiling community-level factors: a multilevel mixed-effect analysis of eye care service utilization and associated factors in Andabet, Northwest Ethiopia - Asmare, Zufan Alamrie; Tsega, Sintayehu Simie; Moges, Tilaye Arega; Tarekegn, Getachew Yitayew; Damtie, Dejen Gedamu; Bitew, Bayih Endalew; Anberbr, Sisay Sitotaw; Seifu, Beminate Lemma; Dagnew, Fisseha Nigussie (Frontiers in Public Health, 2025)
BackgroundEye care service utilization (ECSU) is vital for preventing and managing visual impairment, yet its uptake remains suboptimal in many low- and middle-income countries, including Ethiopia. Visual impairment imposes significant economic and social burdens, much of which is preventable with timely screening and treatment. Despite previous studies on ECSU, gaps remain in understanding individual- and community-level factors influencing its use in specific regions. This study aimed to determine the magnitude and associated factors of eye care service utilization (ECSU) among older adults in the Andabet District, Northwest Ethiopia.MethodA community-based cross-sectional study was carried out among older adults from May 1–30, 2024 in Andabet District, Northwest Ethiopia. Multistage systematic random sampling was employed to reach 570 older adults. A multilevel mixed-effect logistic regression analysis was employed to assess both individual and community-level factors associated with ECSU. We fitted both random-effect and fixed-effect analysis. Finally, variables with p < 0.05 in the multivariable multilevel mixed-effect analysis were claimed to be significantly associated with ECSU.ResultIn this study, the good level of ECSU was found to be 16.14% (95% CI: 13.11, 19.16). In the multilevel mixed-effect logistic regression analysis, aged ≥ 65 years (AOR = 4.59; 95% CI: 1.38, 15.21), having health insurance (AOR = 1.98, 95% CI: 1.51, 2.58), living nearer to eye care facility (AOR = 6.42, 95% CI: 1.95, 21.15), and having awareness about regular eye checkups (AOR = 1.63; 95% CI: 2.88, 9.70) were significantly associated with good level of ECSU.ConclusionIn this study, the magnitude of eye care service utilization was lower than in other studies. Age, health insurance, distance from the eye care facility, and awareness were independent determinants of ECSU. Therefore, policymakers should prioritize accessible health insurance and expand eye care facilities, especially in rural areas. Integrating routine eye exams into primary care and launching widespread awareness campaigns can promote preventive eye health. A unified, multi-sectoral strategy focused on access, integration, and education is key to enhancing ECSU.